IMPROVING HYGIENE CHARACTERISTICS OF PREVENTING ILLNESS AND HEALTH OF PREMATURE CHILDREN - Sagdullaeva M.A. (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Purpose: to improve the hygienic features of treatment and prevention of health condition and developmental defects of premature children. Materials and methods: the main group of premature children (226 people), the healthy control group (68 people) and the control group (68 people) who were treated in the department of infant diseases of the multidisciplinary hospital of the Tashkent Medical Academy, are the children’s research object. Analytical, hygienic, anthropometric, biochemical, clinical and statistical research methods were used in the research. Results: an algorithm for assessing the health status and disease risk factors of premature children, and the hormonal development of premature children was developed. Scientifically based recommendations have been developed on the organization of optimal daily hygienic conditions and treatment procedures for children born after the term.